Queer silence : on disability and rhetorical absence - Smilges, J. Logan (University of Minnesota Press, 2022)
While silence is often linked to voicelessness, complicity, and even death in queer culture, Queer Silence insists that silence can be a generative and empowering mode of survival. Triangulating insights from queer studies, disability studies, and rhetorical studies, J. Logan Smilges explores what silence can mean for people whose bodyminds signify more powerfully than their words.--